Analisa Peningkatan Efisiensi Direct-Fired Heater - Anam, Choirul (Institut Teknologi Indonesia, 2018)
Direct-Fired Heater, usually called heater is a heat exchanger equipment that use hot gasses from combustion to rise up process fluid temperature flow through tubes coil in the heater. Debutanizer Reboiler Heater at PT Pertamina Balikpapan Refinery, having capacity 137,185,000.00 Btu/h was replaced and need efficiency improvement both in heat absorption and fuel consumption. That’s why; need to analyze the existing design. The analysis method is using Microsoft Excel Programming Software base on API 560, API 530, Direct-Fired Heater Design Handbook and literatures from journals and articles. For efficiency improvement in heat absorption and fuel consumption, need to modify heating surface area and combustion air input at elevated temperature. So, by adding Air-Preheater for rise up combustion air input by using stack flue gas, the fuel combustion can be decreased and heat liberated increased.